SISTEM INFORMASI PENYEWAAN GEDUNG SERBAGUNA BERBASIS PROGRESSIVE WEB APP DI KOTA PONTIANAK - Rezza Maulana; Yus Sholva; Morteza Muthahhari (PT. Hasba Edukasi Mandiri, 2025)
The rental of multipurpose buildings is a significant need for the community in Pontianak City for various events such as weddings, seminars, and other activities. However, the manual rental process often leads to inefficiencies, such as limited information, recording errors, and difficulties in coordination between tenants and building managers. This research aims to develop a multipurpose building rental information system based on a Progressive Web App (PWA) that facilitates the rental process. The system is designed to provide real-time access for users, offering transparent information on building availability, schedules, facilities, and pricing. The application utilizes PWA technology, enabling access via browsers and installation as a native-like application. It also includes a search feature to find buildings based on building name, event type, rental date, and price to enhance user convenience and comfort. Testing was conducted using the black box testing method to ensure functionality and the Likert scale assessment to evaluate user satisfaction with the developed system. The results of this study indicate that the multipurpose building rental information system based on Progressive Web App significantly improves the efficiency and effectiveness of the rental process, enhances user experience, and assists building managers in managing rental data in a structured and integrated manner.